Kinetics of DNA thermal stability in the presence of cisplatin - D. Y. Lando; I. E. Grigoryan; E. N. Galyuk; A. S. Fridman; Y. B. Dalyan; S. G. Haroutiunian (ՀՀ ԳԱԱ հրատ.)
Antitumor drug cisplatin forms in DNA intermediate monofunctional and final bifunctional adducts that produces strong structural distortions to the double helix. To study the influence of both distortions on DNA thermal properties, we have monitored δTm(t) that is the time dependence of a change in DNA melting temperature under incubation with cisplatin. Հակաուռուցքային դեղանյութ հանդիսացող ցիսպլատինը կապվում է ԴՆԹ-ի հետ` առաջացնելով միջանկյալ մոնոֆունկցիոնալ և վերջնական բիֆունկցիոնալ ադուկտներ, որոնք բերում են երկպարույրի կառուցվածքային խախտմանը: Противоопухолевый препарат цисплатин связывается с ДНК, образуя промежуточные монофункциональные и конечные бифункциональные аддукты, которые приводят к сильным структурным искажениям двойной спирали.
Keywords: Biology; Biochemistry